Use of YouTube to watch health-related videos and participation in online support groups among US adults with heart disease, diabetes, and hypertension. (August 2022) - Langford, Aisha T; Orellana, Kerli T; Buderer, Nancy
Objective: Social media use has grown over time. However, it is unclear how people with a self-reported history of cardiovascular disease or cardiovascular disease-related risk factors such as diabetes and hypertension use social media. Methods: Data from the 2020 Health Information National Trends Survey (HINTS 5, Cycle 4) were analyzed (N = 3865). Only respondents with complete data for all variables of interest were included in the analyses, resulting in 306 respondents with a heart condition, 1291 with hypertension, and 608 with diabetes. We explored associations between two dependent variables: (1) participated in an online forum or support group and (2) watched a health-related video on YouTube, and sociodemographic factors and patient-provider communication. Analyses were conducted separately by medical condition. Odds ratios, 95% confidence intervals, and p -values were calculated. Results: In respondents with a heart condition, hypertension, or diabetes, 5.4%, 8.4%, and 10.3% had participated in an online support group and 29.6%, 40.4%, and 36.6% had watched health-related videos on YouTube, respectively. Univariately, the odds of using online support groups was associated with younger age (vs. > = 65) in people with a heart condition and hypertension, but not diabetes. Regarding YouTube, younger age was associated with watching health-related videos across all three medical conditions, with additional gender and education associations observed in those with hypertension. There were no associations between social media use and patient-provider communication. Conclusions: These findings may inform the selection of social media platforms for behavioral interventions depending on the intended patient population and goals (e.g. social support vs. video-based health education).